The Impact of COVID-19 on Food Security and Nutrition in Pakistan: A Narrative Review - Quraishi, Uzma; Ali , Hina; Bajwa, Ruqia Safdar; Bibi, Asia (South Asian Journal of Social Sciences and Humanities, 2020)
Covid-19 pandemic impact on food security and nutrition is a global occurrence that is increased domestically as well as economically. The impact of COVID-19 on food security and nutrition is harmful. The primary risk to food security is at the country level. Covid-19 pandemic has sparked health and economic crisis. The supply chain is disrupted due to the lockdown situation and unemployment in the country. Loss of incomes and remittances are creating immense food security risks in Pakistan. The purpose of this study is to analyze the impact of COVID-19 on food security and nutrition in Pakistan. People want fresh and healthier food but the food industry is unable to achieve challenges due to lack of resources and finance. The income level of the people became near to the ground due to lockdown in the country. People’s power of purchasing and spending on food is low, as a result, the demand for the product is fewer and the industry supply chain is being affected day by day. Due to the impact of COVID-19 and lockdown, the food insecurity grew up since there is an increase in daily base goods like fruit, milk, and vegetables, etc. The chance of food insecurity and depletion increased due to COVID-19 and lockdown. Thousand of deaths were reported in the world due to food insecurity and pandemic illness. The risk for food insecurity increases when money to buy food has limited The findings of the study show that the impact of COVID-19 on food security and nutrition is more rigorous and severe. Food insecurity affects the human life of young, old, children and pregnant women, etc.the reason is that food, nutrition, health, unemployment, and socio-economic outcomes are interlinked.